Self‐Assembled Fullerene Nanostructures: Synthesis and Applications. (27th October 2021) - Baskar, Arun V.; Benzigar, Mercy R.; Talapaneni, Siddulu Naidu; Singh, Gurwinder; Karakoti, Ajay S.; Yi, Jiabao; Al‐Muhtaseb, Ala'a H.; Ariga, Katsuhiko; Ajayan, Pulickel M.; Vinu, Ajayan
Abstract: Functionalized fullerene nanostructures are a distinct class of materials that exhibit the combined properties of both fullerene and nanostructures including excellent optoelectronic features, modified band edges, high electron affinity, fast charge transfer capabilities, and tunable structural and textural properties. These fascinating properties allow for their utilization in many applications such as polymer solar cells, photovoltaics, photocatalysis, photodynamic therapy, electrocatalysis, environmental remediation, and drug and gene delivery. Numerous synthesis methods and anchoring groups are employed for functionalized fullerenes with nanostructures by using convergent bottom‐up and top‐down strategies. The supramolecular self‐assembly and functionalization of fullerenes through robust chemistry approaches such as surface oxidation, grafting, polymer coating, doping of metals/nonmetal heteroatoms, noncovalent modification with 2D materials and nanoparticle attachment result in achieving fine control over its surface and bulk properties, including increased solubility, wettability, electron transport, acid–base properties, adsorption, electronic conductivity, and light absorption. This review analyzes the salient developments in the fabrication of nanostructured fullerenes and their functionalized derivatives for many applications including adsorption, catalysis, sensors, energy storage, solar cells, drug delivery, magnetic and superconducting devices. The contents of this review will allow the readers to cherish exciting possibilities and opportunities in field of functionalized nanofullerenes. Abstract : The design strategies and preparation methods including predesigned and postsynthetic strategies for the construction of fullerene‐based nanoarchitectures with diverse morphologies, architectures, and dimensionalities are presented. Their performance in high‐throughput applications with an in‐depth understanding of the structure–property relationships is provided along with future challenges.